MODERN PROBLEMS OF TEACHING RUSSIAN IN FOREIGN LANGUAGE GROUPS OF PEDAGOGICAL UNIVERSITIES - Касымова Феруза Суннатовна (Web of Journals Publishing, 2025)
This article discusses the key problems affecting the effectiveness of language teaching. The causes of key problems related to teaching are identified, the main difficulties in teaching Russian in a foreign language classroom are identified.